PODI AND ODI IN CLAUSE CONSTRUCTION OF KEMAK - Budiarta, I Wayan; Artawa, Ketut; Mbete, Aron Meko; Sri Satyawati, Made (e-Journal of Linguistics; Vol. 7. Juli 2013 No. 2, 2013)
This article reveals podi and odi in clause construction of Kemak. Specifically, this article is aimed at finding out in what construction   podi and odi appear. Moreover, this article is also aimed at finding out the function of podi and odi in the clause construction of Kemak. Before exploring podi and odi in clause construction, the first discussion will examine the morphology of the verb of Kemak to find out how the verbs are formed in Kemak as they have the main role to fill the predicate. The discussion continues to examine the clause with nonverbal (verbless) and verbal predicate. Clause with nonvebral (verbless) predicate will begin the discussion on clause construction in Kemak. Then, the discussion goes to clause with verbal predicate. The clause with verbal predicate includes intransitive and transtive. The disscussion of transitive clause covers monotransitive and  ditransitive clause. The  study on transitive clause is related to the presence of podi and odi in the construction.The result shows that all verbs are basic verbs. Verbs in Kemak are morphologically unmarked (no affixes) and there is no agreement between the verb and its arguments. The clause with nonverbal predicate in Kemak is filled by  noun, adjective, numeral, and prepositional phrase. Clause with nonverbal predicate requires one argument  functioning as grammatical subject. As cluase with nonverbal predicate, intransitive clause in Kemak also requires one argument  functioning as grammatical subject. Meanwhile, monotransitive clause requires two arguments, preverbal and postverbal argument. Ditranstive clause requires three arguments, one preverbal and two postverbal argument. Moreover, it was found that   podi appears in ditransitive clause (applicative/benefactive construction). Podi has the function to increase the verb valence from monotransitive into ditransitive. Meanwhile, odi appears in monotransitive clause  The presence of odi in monotrasitive is as the alternation result from ditransitive clause into monotransitive clause. Moreover, odi has the function to decrease the number of core argument, from three core arguments to two core arguments.
Keywords: podi, odi, clause construction, monotransitive, ditransitive, Kemak